Embolization coils in treating postoperative bronchopleural fistula: a systematic review - Luo, Xiaojuan; Zhan, Ke; Bai, Yang (Frontiers in Medicine, 2024)
Objective This study aims to comprehensively evaluate embolization coils in treating postoperative bronchopleural fistula (BPF). Methods A systematic review based on PubMed, Embase, and The Cochrane Library studies was conducted. All cases receiving embolization coils in treating postoperative BPF were included. The primary outcome was the efficacy of embolization coils in achieving closure of postoperative BPF. Results 20 patients from 9 studies were included in this systematic review. A median number of 3 (range: 1–10) embolization coils with sealants obtained a complete closure rate of 80% in patients with postoperative BPF with sizes ranging from 2 to 3.1 mm. Three patients with BPF over 3 mm and one with multiple organ failure failed this treatment. Two cases of coil migration were reported without causing respiratory failure or fistula recurrence. Conclusion Embolization coils might be considered a safe and effective bronchoscopic treatment for small postoperative BPF of less than 3 mm in size. More extensive and rigorous studies are needed to further evaluate and confirm the optimal use of embolization coils in the context of an alternative to surgical repair.